Está en la página 1de 3

8.

Encuentre la solucin para la siguiente ecuacin con valor absoluto y


compruebe su solucin:
{ X2 - 6x + 5 } = 4

X2 - 6x + 5 = 4
X2 - 6x = 4 5
X2 - 6x = - 1
x=

6 (6)24 . 1. 1
2. 1

6 (6)24
x=
2.1

x=

6 (6)24
2

6 62 4
x=
2

x=

6 32
2

x=

6 16 . 2
2

x=

6 42
2

6 4 2
x=
2
2
x=3

4 2
2

x=3 2 2

x=3+2 2

x=32 2
x

= 3 2 2 , 3 + 2 2

X2 - 6x + 5 = - 4
X2 - 6x = - 4 5
X2 - 6x = - 9
6 (6)24 . 1. 9
x=
2 .1

x=

6 (6)24 . 9
2 .1

6 (6)24 . 9
x=
2 .1

x=

6 (6)24 . 9
2

x=

6 62 4 . 9
2

x=

6 3636
2

x=

6 0
2

x=

6 0
2

x=

6
2

x=3